Innovation reliability and variability strategies: the importance of absorptive capacity on systemic outcomes - Pinheiro, J.; Lages, L. F.; Dias, Á.; Silva, G. M.; Preto, M. T. (International Journal of Knowledge-Based Development, 2020)
The role of absorptive capacity (AC) has been widely recognized in the innovation literature. This study examines the predictive role of AC for business performance, and evaluates the mediation of market orientation (responsive-proactive) and innovation competences orientation (exploitation-exploration) in that relationship. It addresses the gap in the literature on the relative importance of innovation competence orientations versus market orientations. The findings show that innovation competence orientations are more important to business performance than market orientations and that innovation competences are better enhanced by AC than by market orientations. AC is not only confirmed as an antecedent of ambidextrous market and innovation competence orientation, but it also helps directly and indirectly to explain business performance. Responsive market orientation and innovation competence orientation mediate the positive relationship between AC and business performance. The intensity and significance of the indirect effects reveal the specific knowledge-transformative roles of market and innovation competences orientations. Firms seem to mitigate uncertainty by adjusting their preferences toward less risky innovation strategies. Managerial implications highlight the relevance of innovation competences orientation versus market orientation. Furthermore, firms seem to use proactive market orientation ineffectively, a finding that signals a structural marketing handicap.